2016
DOI: 10.4236/jmp.2016.712128
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pico-Second Pulse Electron Irradiation on the Electrical-Physical Properties of Silicon Crystals

Abstract: The studies of the influence of pico-second (4 × 10 −13 sec.) pulse electron irradiation with energy of 3.5 MeV on the electrical-physical properties of silicon crystals (n-Si) are presented. It is shown that in spite of relatively low electron irradiation energy, induced radiation defects are of cluster type. The behavior of main carrier mobility depending on temperature and irradiation dose is analyzed and charge carriers' scattering mechanisms are clarified: on ionized impurities, on point radiation defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In previous studies, we have shown that the application of pico-second duration pulse irradiation mainly generates A-centre type defects (in the form of clusters) in n-Si crystals [12], and in the following, we describe measurements of this center specifically. In the current paper a determination is made of the conductivity, concentration of charge carriers, their mobility, the lifetime of the minority charge carriers, in irradiated samples, and a detailed analysis of the results was made in order to elucidate the nature of the recombination centers.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous studies, we have shown that the application of pico-second duration pulse irradiation mainly generates A-centre type defects (in the form of clusters) in n-Si crystals [12], and in the following, we describe measurements of this center specifically. In the current paper a determination is made of the conductivity, concentration of charge carriers, their mobility, the lifetime of the minority charge carriers, in irradiated samples, and a detailed analysis of the results was made in order to elucidate the nature of the recombination centers.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 96%
“…The formation of a non-equilibrium state in irradiated host crystals is well known [7] [8] [9]; however only a few initial investigations have been made using radiation applied at very short pulse durations [10] [11] [12], whereas such investigations are highly demanded both in theory and practice, particularly in space applications. The concept of a non-equilibrium state provides a basis for reinterpretation of the following radiation effects: formation of stable state of the crystal properties; differences in the radiation, thermal and time stability of materials with different impurity contents; injection of impurity atoms into the positions where intrinsic interstitial atoms are trapped; and thermal processes that occur in irradiated crystals: the latter is not feasible in the current study, because the thermal processes are not activated on the short timescale of pico-second pulse irradiation [11].…”
Section: Introductionmentioning
confidence: 99%